2007
DOI: 10.1063/1.2697551
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and band gap determination of HfO2 thin films

Abstract: Valence electron energy loss spectroscopy ͑VEELS͒ and high resolution transmission electron microscopy ͑HRTEM͒ are performed on three different HfO 2 thin films grown on Si ͑001͒ by chemical vapor deposition ͑CVD͒ or atomic layer deposition ͑ALD͒. For each sample the band gap ͑E g ͒ is determined by low-loss EELS analysis. The E g values are then correlated with the crystal structure and the chemical properties of the films obtained by HRTEM images and VEELS line scans, respectively. They are discussed in comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
71
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(83 citation statements)
references
References 31 publications
4
71
1
Order By: Relevance
“…8. The obtained result indicated an E g of 5.1 eV which is lower than those reported in the literature [27,28]. A possible explanation for this phenomenon can be due to oxygen vacancies, distortions on the [HfO 6 ], intrinsic surface effects, etc.…”
Section: Resultscontrasting
confidence: 59%
“…8. The obtained result indicated an E g of 5.1 eV which is lower than those reported in the literature [27,28]. A possible explanation for this phenomenon can be due to oxygen vacancies, distortions on the [HfO 6 ], intrinsic surface effects, etc.…”
Section: Resultscontrasting
confidence: 59%
“…We observe in particular a different attribution of the intensity of the plasmon at ∼16 eV, which is the most intense peak e.g. in Cheynet et al 40,41 , while it is less intense than the collective excitation at ∼27 eV in Park and Yang 37 . We observe different intensities also on the 47 eV LF-damped plasmon.…”
mentioning
confidence: 62%
“…Although mechanical compression of the nanoparticles thin films leading to an increase of the measured dielectric constant was adopted as a method for confirming the presence of air voids in the film as responsible for the measured low value of the dielectric constant, however compression of the film might have an obvious effect in the shape and size/size distribution of the nanoparticles or even in their crystal structure. For instance, previous studies have shown that the interface strain of hafnia nanoparticles thin film with the underlying substrate causes the presence of cubic and tetragonal phases in addition to the monoclinic phase [63,1]. Compression of the nanoparticles film might induce a mechanical stress in the nanoparticles and also lead to a deformation of the shape of the nanoparticles and/or causing the nanoparticles to effectively join together in the form of a bulk material thus resulting to a change of the crystal structure of the nanoparticles as that was originally formed by the synthesis conditions.…”
Section: Dielectric Properties Of Hafnia Nanoparticlesmentioning
confidence: 99%